Reducing Physician Assistant National Certifying Exam Failures Through Targeted Interventions. - Gentry, Ashley; McGuffee, America (Journal of Physician Assistant Education (Lippincott Williams & Wilkins), 2025)
Introduction : In partial fulfillment of accreditation requirements, physician assistant (PA) programs analyze various performance indicators to identify correlation to Physician Assistant National Certifying Exam (PANCE) outcomes. While numerous studies have identified correlating performance indicators, research defining actionable, program-specific intervention criteria is limited. To address this need, we aim to determine if interventions implemented by the program based on indicator cutpoints were effective in reducing the number of potential PANCE failures. Methods: This retrospective study includes students in cohorts 2019 to 2024 from the University of North Texas Health Science Center PA Program (n = 426). Pearson correlation and regression analysis was performed to identify cutpoints for program indicators of PANCE performance. At-risk student performance after counseling and intervention was then analyzed. Results: Students with 5 or more indicators below the cutpoint were projected to fail the PANCE. Cohorts 2019 to 2023 had 5 or fewer projected PANCE failures each year, while cohort 2024 had 13 projected failures. With targeted intervention and counseling initiated early in the program, the 2024 cohort had a significantly lower rate of PANCE failure among those projected to fail compared to previous cohorts (2024: 8%; 2023: 50%; 2021: 40%; 2020: 50%). Discussion : Monitoring student progress through both didactic and clinical phases, using a combination of cutpoints for programmatic assessments and course performance, allows for timely and individualized interventions that can enhance PANCE pass rates. The noted reduction in the PANCE failure rate for cohort-specific high-risk students highlights the success of this approach and underscores the value of personalized counseling, tailored interventions, and access to resources throughout the program.